Imams as Bridge Builders for the Integration (KULT_online, 2011)
In his book Die Prediger des Islam (Preachers of Islam: Imams  – who they are and what they really want), Rauf Ceylan, lecturer of Religious Studies at Osnabrück University, presents the results of many years of field study. It is one of the first comprehensive look dealing with the function imams fulfil at Turkish mosques in Germany. By means of numerous interviews it offers an insight into the topic of imams and their role for the integration of Muslim immigrants. The book contains exact typologies of the imams preaching in Germany and emphasises their function as an important link between mosque community members and the German majority society. Ceylan wants to initiate a discussion in society and therefore consciously writes in the style of popular science. However, in the light of the recent developments his proposals for solutions do not offer any new guidelines for the German politics on Islam, in spite of powerful arguments, like the one that imams who were educated at German universities are essential for the establishment of Islam in Germany. Nevertheless, the book remains an important contribution to the current debate on integration and Islam.